Hungarian Monitoring, 20 June 1988 . [Magyar rádiófigyelő], 1988. június 20 - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
Transcripts of Hungarian national radio programs produced by the Hungarian Monitoring Unit of Radio Free Europe/Radio Liberty. A magyar országos rádióadók műsorainak a Szabad Európa Rádió/Szabadság Rádió Magyar Monitoring Osztálya által készített átiratai. International Politics: - 14 most developed countries hold summit in Toronto - More West German credit for the GDR - Sino-Soviet talks in Moscow Domestic Affairs: - Károly Grósz receives the president of the Egyptian parliament - Hungarian-Finnish relations - Soviet military delegation in Budapest - Film and TV Artists' Association suggests placing Romanian village destruction policy on UN and Warsaw Pact agendas - Mátyás Szűrös at Berlin nuclear-free zone talks - Mihály Károly Society formed Economy: - “Innovation in small private companies” - Conference Külpolitika: - A tizennégy legfejlettebb ország torontói csúcsértekezlete - Újabb nyugatnémet hitel az NDK-nak - Szovjet-kínai megbeszélések Moszkvában Belpolitika: - Grósz Károly fogadta az egyiptomi parlament elnökét - Magyar-finn kapcsolatok - Szovjet katonai küldöttség Budapesten - A Film és TV Művészek Szövetsége a romániai falucsökkentési program ügyének az ENSZ és VSZ napirendjére való tűzését javasolja - Szűrös Mátyás a berlini atomfegyver mentes övezetek tanácskozásán - Megalakult a Károlyi Mihály Társaság Gazdaság: - "Innováció a magán kisvállalkozásokban" - Konferencia